INTERNATIONALIZATION OF HIGHER EDUCATION AND ITS IMPACT ON THE FORMATION OF COMPETENCES OF FUTURE SPECIALISTS - Кінаш, Ірина Петрівна; Берлоус, Марія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The aim of the article is to study the features of the manifestation of the internationalization of domestic higher education and to identify the competencies that should be formed in future specialists in order to adapt them to the conditions of work in the global labour market. The work uses methods of analysis, synthesis and generalization. It is established that the internationalization of higher education involves strengthening the international component in the activities of institutions for their cooperation. The main manifestations of the internationalization of domestic higher education are highlighted. The most common manifestation is international academic mobility, which has led to student migration. It is established that during 2009-2024 the number of Ukrainians studying at Western universities increased more than fivefold. This trend is due to the solidarity and support of the academic community of Ukrainian educational institutions, good training of students, as well as a significant number of international mobility projects won within the framework of the EU Erasmus+ program. It was found that the internationalization of education is a powerful tool for developing competencies. The study indicated that those students who took advantage of academic mobility programs showed better results in general (analytical skills, problem-solving skills, communication skills) and professional competencies (international competencies). These students also demonstrated better foreign language proficiency, knowledge and understanding of international differences in culture and society, the ability to work with people with different cultural backgrounds, and broader professional knowledge of other countries. It was concluded that the internationalization of higher education leads to the need for students to acquire new competencies. Global competence is identified, which can be formed in the synergy of intercultural and linguistic competence. Its manifestation will be observed in professional socio-cultural competence. This competence will determine the ability of higher education students to adequately absorb professional information and communicate in a multicultural environment.